Características, impactos y antecedentes del modelo de liderazgo escolar transformacional (Characteristics, impacts and background of the transformational school leadership model) - Sun, Jingping (Revista Eletrônica de Educação, 2019)
Based on research evidence from the origins of transformational leadership in the seventies, the author claims that this approach is the one that presents the highest incidence in the policies of promotion of school leadership and the one that has the largest number of empirical studies carried out. His chapter analyzes the evidence regarding the strong influence of transformational leadership of managers in the emotional state of teachers, their job satisfaction and their commitment to school, as well as its relevant effect on the practices that teachers perform, reviewing its effect regarding the academic results of the students, which would also affect, although in a milder way, through the teachers. Resumo Com base em evidências de pesquisas sobre as origens da liderança transformacional nos anos setenta, o autor assegura que essa abordagem é a que apresenta maior incidência nas políticas de promoção de liderança escolar e aquela que possui o maior número de estudos empíricos realizados. Seu artigo analisa evidências sobre a forte in?uência transformacional da liderança dos gestores no estado emocional, na satisfação com o trabalho e no compromisso dos professores com a escola, bem como seu efeito relevante nas práticas que os professores realizam, revendo seu efeito nos resultados acadêmicos dos alunos, o que também afetaria, ainda que de forma mais branda, através dos professores. Resumen A partir de la evidencia de investigaciones desde los orígenes del liderazgo transformacional en los años setenta, la autora asegura que este enfoque es el de mayor incidencia en las políticas de fomento del liderazgo directivo escolar y el que tiene el mayor número de estudios empíricos realizados. Su capítulo analiza la evidencia respecto a la fuerte incidencia del liderazgo transformacional de los directivos en el estado emocional de los docentes, su satisfacción laboral y su compromiso con la escuela, así como su efecto relevante en las prácticas que los docentes realizan, revisando su efecto respecto los resultados académicos de los alumnos, en los que también incidiría, aunque de modo más leve y a través de los docentes. Keywords: Transformational leadership, Teaching practices, Leadership effect, Academic results of the students. Palavras-chave: Liderança transformacional, Práticas de ensino, Efeito de liderança, Resultados acadêmicos dos alunos. Palabras claves: Liderazgo transformacional, Docentes prácticas, Liderazgo efecto, Resultados académicos de los alumnos. References ANTONAKIS, J.; CIANCIOLO, A. T.; STERNBERG, R. J. Leadership: Past, present and future. In: ANTONAKIS, J.; CIANCIOLO, A. T; STERNBERG, R. J. (Eds.), The nature of leadership. Thousand Oaks: Sage, 2004, pp. 3-13. AVOLIO, B. J.; BASS, B. M. Re-examining the components of transformational and transactional leadership using the multifactor leadership. Journal of Occupational and Organizational Psychology, 72, 1999, pp. 441-462. AVILA, S. The relationship between deans’ transformational leadership skills and student graduation rates in vocational colleges, disertación, Brandman University, Irvine, CA (disponible en la base de datos de disertaciones y tesis ProQuest: Texto completo, Publicación No. AAT 10036397, 2016. BASS, B. M.; AVOLIO, B. J. Improving organizational effectiveness through transformational leadership. Thousand Oaks, CA: Sage, 1994. BASS, B. M.; AVOLIO, B. J. Manual for the multifactor leadership questionnaire. Palo Alto, CA: Mind Garden, 1996. BASS, B. M. The ethics of transformational leadership. KLSP: Transformational Leadership, Working Papers. Academy of Leadership Press, 1997. Consultado el 25 de diciembre de 2006 en http://www.academy.umd.edu/publications/klspdocs/bbass_p1.htm BASS, B. M.; AVOLIO, B. Multifactor leadership questionnaire: Technical report (2a. ed.). California: Mind Garden, 2000. BASS, B. M.; STEIDLMEIER, P. Ethics, character, and authentic transformational leadership. 1998, September, 24. Consultado el 3 de junio de 2002 en http://cls.binghamton.edu/BassSteid.html BELL, L.; BOLAM, R.; CUBILLO, L. A systematic review of the impact of school headteachers and principals on student outcomes. Londres: EPPI-Centre, Social Science, Research Unit, Institute of Education. 2003. Consultado el 4 de febrero de 2010 en http://eppi.ioe.ac.uk/cms/Default.aspx?tabid=317 BEVERBORG, A. O. G.; SLEEGERS, P. J. C.; ENDEDIJK, M. D.; VEEN, K. V. Towards Sustaining Levels of Reflective Learning: How Do Transformational Leadership, Task Interdependence, and Self-Efficacy Shape Teacher Learning in Schools, Societies, 5(1), 2015, pp. 187-219; doi:10.3390/soc5010187. BROWN, L. I. A meta-analysis of research on the influence of leadership on student outcomes.Tesis de doctorado. Instituto Politécnico de Virginia y State University, Estados Unidos, 2001. BURNS, J. M. Leadership. Nueva York: Harper and Row, 1978. CHIN, J. P. Meta-analysis of transformational school leadership effects on school outcomes in Taiwan and the USA. Asia Pacific Education, 8 (2), 2007, pp. 166-177. COHEN, J. Statistical power analysis for the behavioral sciences. (2a ed.). Hillsdale, NJ: Erlbaum, 1988. HALLINGER, P. The evolving role of American principals: From managerial to instructional to transformational leaders, Journal of Educational Administration, Vol. 30 No. 3, 1992, pp. 35-50. HALLINGER, P.; HECK, R. H. Exploring the Principal’s Contribution to School Effectiveness: 1980-1995. School Effectiveness and School Improvement, 9(2), 1998, pp. 157-191. HALLINGER, P.; WANG, W. C.; CHEN, C. W. Assessing the measurement properties of the Principal Instructional Management Rating Scale: A meta-analysis of reliability studies, Educational Administration Quarterly, Vol. 49 No. 2, 2013, pp. 272 -309. JANTZI, D.; LEITHWOOD, K. Toward an explanation of variation in teachers’ perceptions of transformational school leadership. Educational Administration Quarterly, 32 (4), 1996, pp. 512- 538. JUDGE, T. A.; PICCOLO, R. F. Transformational and transactional leadership: A meta-analytic test of their relative validity. Journal of Applied Psychology, 89(5), 2004, pp. 755-768. KOUZES, J.M.; POSNER, B.Z. Leadership Practices Inventory. A Self-assessment and Analysis, edición aumentada, Jossey-Bass, San Francisco, CA, 1993. KOUZES, J. M.; POSNER, B. Z. The leadership challenge: How to keep getting extraordinary things done in organizations (Revised ed.). San Francisco, CA: Jossey-Bass, 1995. LEITHWOOD, K. Leadership for school restructuring. Educational Administration Quarterly, 30, 1994, pp. 498-518. LEITHWOOD, K.; DUKE, D. A century’s quest to understand school leadership. In J. Murphy, & K. S. Louis (Eds.), Handbook of research on educational administration. San Francisco: Jossey-Bass, 1999, pp. 45-72. LEITHWOOD, K., & JANTZI, D. Transformational leadership: How principals can help reform school cultures. School Effectiveness and School Improvement, 1(4), 249-280, 1990. LEITHWOOD, K., & STEINBACH, R. Indicators of transformational leadership in the everyday problem solving of school administrators. Journal of Personnel Evaluation in Education, 4, 221-244, 1991b. LEITHWOOD, K.; TOMLINSON, D.; GENGE, M. Transformational school leadership. In: LEITHWOOD (Ed.), International handbook of educational leadership and administration. Países Bajos: Kluwer Academic, 1996, pp. 785-840. LEITHWOOD, K.; JANTZI, D. Explaining variation in teachers’ perceptions of principals’ leadership: A replication, Journal of Educational Administration, Vol. 35 No. 4, 1997, pp. 312-331. LEITHWOOD, K.; JANTZI, D. The relative effects of principal and teacher sources of leadership on student engagement with school, Educational Administration Quarterly, Vol. 10 No. 4, 1999, pp. 451-479. LEITHWOOD, K.; JANTZI, D. Transformational school leadership effects: A replication. School effectiveness and school improvement, 10(4), 1999, pp. 451-479. LEITHWOOD, K..; JANTZI, D. The relative effects of principal and teacher sources of leadership on student engagement with school. Educational Administration Quanterly, 35, 2000, pp. 679-706. LEITHWOOD, K.; LOUIS, K.; ANDERSON, S.; WAHLSTROM, K. How leadership influences student learning: A review of the evidence linking leadership to student learning. Nueva York: the Wallace Foundation, 2004. LEITHWOOD, K.; SAMMONS, P.; ANDERSON, S.; WAHLSTROM, K. How Leadership Influences Student Learning. The Wallace Foundation. Ontario: Center for Applied Research an Educational Improvement / Ontario Institute for School Leadership, 2004. LEITHWOOD, K.; JANTZI, D. A review of transformational school leadership research. Paper presented at the annual meeting of the American Educational Research Association, Montreal, Canadá, 2005. LEITHWOOD, K.; AITKEN, R.; JANTZI, D. Making school smarter: Leading with evidence (3nd ed.). Thousand Oaks, CA: Corwin Press, 2006. LEITHWOOD, K.; SUN, J. P. Transformational school leadership effects on schools, teachers and students. In W. HOY & M. DIPAOLA (Series Eds.), Research and theory in educational administration. Vol. 8. Studies in school improvement programs. Charlotte, NC: Information Age, 2009, pp. 1-22. LEITHWOOD, K.; SUN, J.- P. The nature and effects of transformational school leadership: A meta-analytic review of unpublished research. Educational Administration Quarterly, 48(3), 2012, pp. 387-423. LEITHWOOD, K.; LOUISE, K. Linking Leadership to Student Learning. Nueva York: the Wallace Foundation, 2012. LI, D.-J. Relationship Analysis Between Principals’ Transformational Leadership, Teachers’ Organizational Commitment and Teachers’ Job Satisfaction of Rural Middle School, tesis de maestría, Soochow University, Suzhou, China (disponible en la excelente base de datos China de disertaciones y tesis: texto completo), 2010. LI, P.; ZHU, D.-Q. Multidimensional measurement of the effectiveness of transformational leadership in Schools, Education Science, 31(1), 2015, pp. 26-32. MARKS; PRINTY. Integrated leadership: How principals and teachers share transformational and instructional influence. Journal of School Leadership. 2003. http://sprinty.wiki.educ.msu.edu/file/view/Transfomational+leadership.pdf MARZANO, R. J.; WATERS, T.; MCNULTY, B. School leadership that works: From research to results. Aurora, CO: ASCD y McREL. 2005. National Policy Board for Educational Administration (2015). Professional Standards for Educational Leaders 2015. Reston, VA: Autor. ROBINSON, V.; LLOYD, C.; ROWE, K. The impact of leadership on student outcomes: An analysis of the differential effects of leadership types. Educational Administration Quarterly, 44(5), 2008, pp. 635-74. ROBINSON, V. Student-Centered Leadership. San Francisco. Jossey- Bass LLibrary in Education, 2011. SASHKIN, M. The visionary leader: Leadership behavior questionnaire. Amherst, MA: Human Resource Development Press, 1990. SASHKIN, A. Transformational leadership approaches: A review and synthesis. In: J. ANTONAKIS; A. T. CIANCIOLO; R. J. STERNBERG (Eds.), The nature of leadership (). Thousand Oaks: Sage, 2004, pp. 171-196. SUN, J.- P.; LEITHWOOD, K. Transformational school leadership effects on student achievement. Leadership & Policy in Schools, 11(4), 2012, pp. 418-451. SUN, J.- P.; LEITHWOOD, K. Leadership effects on student learning mediated by teacher emotions. Societies 5(3), 2015, pp. 566-582; doi:10.3390/soc5030566. TICHY, N. M.; DEVANNA, M. A. The transformational leader. Toronto: John Willey and Sons, 1990. UNDERDUE, M. Y. A meta-analytic review of the relationship between transformational leadership during complex organization change and worker and organizational outcomes in public and private sector organizations. Disertación doctoral, University of La Verne, Estados Unidos, 2005. WATERS, T.; MARZANO, R. J.; MCNULTY, B. McREL’s Balanced Leadership Framework: Developing the Science of Educational Leadership, 2010. Consultado el 1 de marzo de 2010 en http://www.nga.org/cda/files/0404mcrel.pdf. WEBER, M. The Theory of Social and Economic Organization. Nueva York: The Free Press, 1947. WILEY, S.D. School leadership and professional community: Effects on student achievement. Dissertation Abstracts International, 59(10)A, AAI9910535, 1998. WITZIERS, B.; BOSKER, R. J.; KRÜGER, M. L. Educational leadership and student achievement: The elusive search for an association. Educational Administration Quarterly, 39(3), 2003, pp. 398-425. YUKL, G. Leadership in organizations (3a. edición). Englewood Cliffs, NJ: Prentice Hall, 1994.